PLCγ2 and PKC Are Important to Myeloid Lineage Commitment Triggered by M‐SCF and G‐CSF. Issue 1 (January 2014) - Barbosa, Christiano Marcello Vaz; Bincoletto, Claudia; Barros, Carlos Castilho; Ferreira, Alice T.; Paredes‐Gamero, Edgar J.
ABSTRACT Myeloid differentiation is a complex process whereby mature granulocytes or monocytes/macrophages are derived from a common myeloid progenitor through the coordinated action of hematopoietic cytokines. In this study, we explored the role of the Ca2+i signaling transduction pathway in the commitment of hematopoietic stem/progenitor cells to either the monocytic or granulocytic lineage in response to macrophage colony‐stimulating factor (M‐CSF) and granulocyte colony‐stimulating factor (G‐CSF). M‐CSF and G‐CSF induce cell expansion and monocyte or granulocyte differentiation, respectively, without affecting the percentage of hematopoietic progenitor cells. Colony‐forming units (CFUs) and flow cytometry demonstrated the involvement of phospholipase Cγ (PLCγ) and protein kinase C (PKC) in monocyte/granulocyte commitment. In addition, using flow cytometry and RNA interference, we identified PLCγ2 as the PLCγ isoform that participates in this cell expansion and differentiation. Differences in signaling elicited by M‐CSF and G‐CSF were observed. The M‐CSF‐related effects were associated with the activation of ERK1/2 and nuclear factor of activated T‐cells (NFAT); the inhibition of both molecules reduced the number of colonies in a CFU assay. In contrast, using flow cytometry and confocal evaluation, we demonstrated that G‐CSF activated Jak‐1 and STAT‐3. Additionally, the effects induced by G‐CSF were also related with the participation of Ca2+ calmodulin kinase II and the transcription factor PU.1. STAT‐3 activation and the increase of PU.1 expression were sensitive to PLC inhibition by U73122. These data show that PLCγ2 and PKC are important upstream signals that regulate myelopoiesis through cytokines, and differences in M‐CSF and G‐CSF downstream signaling were identified. J. Cell. Biochem. 115: 42–51, 2014. © 2013 Wiley Periodicals, Inc.